Households' Awareness and Willingness to Pay for Domestic Wastewater Services: A Case of Batam City, Indonesia - Alviza Hindrasari; Alin Halimatussadiah^ (Postgraduate Management Journal, 2022)
Most developing countries lack access to a reliable domestic wastewater service. The perception that government should deliver public goods, along with high investment and limited public budget capacity, create barriers for investing in and providing this service. Literatures on the implementation of Polluter-Pays Principles bring the possibility for charging households for wastewater service to recover operational cost and capital cost. This study aims to see the relationship between public awareness and the probability to pay higher for domestic wastewater services using the case of Batam City, Indonesia. Logit regression analysis method is utilized to 663 observations and result shows that households—who realize that domestic wastewater is a source of pollution and the polluter must pay—have a positive relationship with the probability of paying higher for domestic wastewater services. This finding could be an opportunity for charging the externality of water user and increasing economic feasibility for investing in wastewater service.